The process of requesting clinical tests in a reference university laboratory center - MotaghiPisheh, Hadis; Noori Hekmat , Somayeh; Ghorbani Nia, Rahil (Researcher Bulletin of Medical Sciences, 2021)
Background: Simultaneous with other countries, utilization of laboratory tests has increased in Iran. Since understanding the requesting behavior of doctors is a crucial matter, this study conducted in a university reference laboratory center, aiming to assess the process of requesting clinical tests. Materials and Methods: This study was a descriptive cross-sectional study conducted using the census method on 231277 patients of a main referral polyclinic in Kerman. The data regarding the performed tests, the frequency of requesting laboratory tests, and the demographic information about the patients between 2008 and 2012 extracted from the information system of the laboratory. To analyze the data, SPSS 20 and descriptive statistics methods used. Result: Most of the patients were women 16 to 50 years old, and had gone to the clinic only once. Most prescriptions had 50 to 100 tests. General physicians and internists had the highest share of orders and prescription costs. In accordance with rising medical expenses, the prices of laboratory services increased in each year. Conclusion: This study showed that the 80/20 rule applies to prescriptions, since more than 80% of prescriptions made by only 20% of doctors. To change the behavior of requesting laboratory tests, we need to define accurate and tangible criteria for assessing the appropriateness of requesting in clinical guidelines.